Dinamika Kependudukan dan Tantangan Pengembangan Wilayah di Kota Serang - Ramadhan, Fahmi Nadhif; Chaesar, Muhammad Alfi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Serang City as the capital of Banten Province has experienced quite significant population growth in the last two decades. This growth has created new challenges in regional development, both in terms of infrastructure, economy, social, and environment. This study aims to examine the population dynamics in Serang City and the challenges that arise in the regional development process. The method used is qualitative with a literature study approach through secondary data analysis from official government documents, scientific journals, and relevant research reports. The results of the study indicate that the high rate of population growth has not been balanced by optimal regional planning, which causes spatial inequality, pressure on public facilities, and environmental degradation. Therefore, an inclusive, participatory, and population data-based regional development approach is needed to realize sustainable urban planning.